Neuro-Psycholinguistic Analysis of The Asbun Phenomenon among Generation Alpha on Tiktok - Virgin Noor Vadillah; Lusiana Suciati Dewi; Slamet Wahyudi Yulianto (JEPAL (Journal of English Pedagogy and Applied Linguistics), 2026)
This study explores the phenomenon of ‘Asbun’ (speaking without real substance, or "just making noise") among Generation Alpha, approached through a neuro-psycholinguistic lens. Growing up saturated in digital environments, this generation exhibits distinctive speech patterns marked by rapid word retrieval alongside a diminished capacity for verbal self-restraint. The research aims to examine how patterns of digital engagement shape these ‘Asbun’ speech characteristics, and to use this connection as a way of understanding breakdowns in self-regulation during the process of producing language. Employing a qualitative approach, the study draws on five TikTok video transcripts sourced from different accounts (@alinaa_chan, @istrifadhli, @ibuendog, @leehanim, and @mat_pecii), gathered on March 31, 2026. Theoretically, the analysis combines Levelt's (1989) model of speech production with neurocognitive perspectives on Prefrontal Cortex (PFC) function and Theory of Mind (ToM). The results indicate that ‘Asbun’ speech may be better understood as an outcome of disrupted digital cognitive patterns and impaired linguistic self-monitoring, rather than as deliberate rudeness, lthough sociopragmatic and performative interpretations cannot be ruled out. Heavy consumption of short-form digital media appears to speed up access to the mental lexicon, but at the cost of the sociopragmatic filtering typically governed by the PFC. Because the study relies on an exploratory design with a limited dataset and does not independently confirm the ages of the speakers, its conclusions should be read as a theoretical proposition rather than a generalizable empirical finding. Overall, the language patterns identified in Generation Alpha suggest a form of cognitive restructuring, in which the demand for instant digital communication takes precedence over conventional norms of politeness, a shift that carries important implications for both education and social interaction.